2017
DOI: 10.1186/s12933-017-0569-8
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric and asymmetric dimethylarginine as risk markers of cardiovascular disease, all-cause mortality and deterioration in kidney function in persons with type 2 diabetes and microalbuminuria

Abstract: BackgroundTo evaluate symmetric dimethylarginine (SDMA) and asymmetric dimethylarginine (ADMA) as risk markers of cardiovascular disease, all-cause mortality and deterioration in renal function in a well characterised type 2 diabetic population with microalbuminuria and without symptoms of coronary artery disease.Methods200 participants followed for 6.1 years. SDMA and ADMA were measured at baseline. Endpoints included (1) composite cardiovascular endpoint (n = 40); (2) all-cause mortality (n = 26); and (3) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 34 publications
6
40
0
Order By: Relevance
“…Additionally, increased levels of plasma homocysteine have been found to be related to macroalbuminuria in diabetic patients (39). ADMA, on the other hand, has been suggested as a candidate biomarker for diabetic kidney complications, whilst elevated levels of ADMA have been shown to predict a more accelerated course of renal function loss and promoted the development of renal damage (14,15,40). Our results are also in line with literature data showing that bile acid metabolism is altered in T2D patients (41).…”
Section: Feasibility Of the Methods For The Analysis Of Samples From Asupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, increased levels of plasma homocysteine have been found to be related to macroalbuminuria in diabetic patients (39). ADMA, on the other hand, has been suggested as a candidate biomarker for diabetic kidney complications, whilst elevated levels of ADMA have been shown to predict a more accelerated course of renal function loss and promoted the development of renal damage (14,15,40). Our results are also in line with literature data showing that bile acid metabolism is altered in T2D patients (41).…”
Section: Feasibility Of the Methods For The Analysis Of Samples From Asupporting
confidence: 89%
“…Also other metabolites, e.g. 1,5-anhydroglucitol, norvaline and l-aspartic acid, were found to be associated with macroalbuminuric diabetic kidney disease (11,12), while glutamine, glutamic acid and symmetric dimethylarginine (ADMA) were suggested as potentially-predictive biomarkers of diabetic complications (13)(14)(15). Several metabolites (e.g., α-hydroxybutyrate, βhydroxypyruvate and 1,5-anhydroglucitol (1,5-AG)), were associated with regulation of glycemic control (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Zobel and colleagues also demonstrated in a population of patients with type 2 DM with microalbuminuria and without symptoms of coronary artery disease the association of ADMA with all‐cause mortality. …”
Section: Discussionmentioning
confidence: 93%
“…Increased risk of chronic kidney disease (CKD) progression and atherosclerotic cardiovascular events have been shown to be associated with elevated ADMA and SDMA levels 12,13 . Our earlier studies showed that circulatory ADMA had a causative role in the development of DN 14 .ADMA to SDMA ratio (ASR), also known as catabolism index, has been implicated in sepsis, hypertension, malnutrition, and inflammation [15][16][17][18][19] . A direct correlation between malnutrition, inflammatory markers, and ASR was also established in patients undergoing hemodialysis 16 .…”
mentioning
confidence: 99%
“…ADMA to SDMA ratio (ASR), also known as catabolism index, has been implicated in sepsis, hypertension, malnutrition, and inflammation [15][16][17][18][19] . A direct correlation between malnutrition, inflammatory markers, and ASR was also established in patients undergoing hemodialysis 16 .…”
mentioning
confidence: 99%